Death Instinct Manifested through Passive Aggresiveness and Its Social Effects in Melville's "Bartleby the Scrivener" (NOBEL: Journal of Literature and Language Teaching, 2017)
Death instinct is a lifeless drive in human mind that certainly can affect behavior. This instinct can be manifested through passive aggressiveness that is not easily noticed but will slowly bring loss to everyone involved. In deeply understanding this matter, this paper attempts to analyze the death instinct manifested through passive-aggressiveness by depicting a short story entitled â€œBartleby the Scrivener.â€ To do that, this paper will first examine Bartleby's behaviors that indicate passive aggressiveness. Furthermore, it will explore how Bartleby's passive aggressiveness affects people around him. The result of this analysis shows that Bartleby's death instinct which leads him into death is caused by his persistence to have a static life. This form of passive agrresiveness kills his social life and brings anxiety, confusion, and anger to people who interact with him.